The Effectiveness of KWL and SQ3R Techniques in Teaching Reading Comprehension - Adib - Ahmad (Universitas Pesantren Tinggi Darul Ulum Jombang (Unipdu), 2018)
Reading is considered as an important aspect for students because of its valuable benefit in developing knowledge. There are approaches of reading such as top-down, bottom up, and interactive approach. Some studies was conducted in applying interactive strategy such as SQ3R technique and KWL technique. For the purpose of teaching narrative, descriptive and news item text, the researcher try to observe and analyze the effectivenes of SQ3R and KWL techniques. The study was conducted at SMA Darussalam Blokagung Banyuwangi. This research used quasi experimental method. The researcher did a treatment by applying KWL technique to the experimental class and SQ3R technique to the control class. The data obtained were calculated by using a t-test for independent sample through SPSS 20 for windows to test the hyphothesis. After applying the statistical computation, the result shows that the probability was ,564 or 5,6 % > 5% and the t value was 0,57 > 0,5. it can be concluded that the difference effect between the two technique is not significant. However, the improvement of the mean obtained by the experimental and control group from pretest and posttest show that there is variance between the students’ starting skill and the students’ achievement after getting the treatments. Thus, the interactive approach by using KWL and SQ3R technique is effective to improve students’ reading skill.